Amyloid fibril-based membranes for PFAS removal from water. Issue 10 (1st September 2021) - Jin, Tonghui; Peydayesh, Mohammad; Joerss, Hanna; Zhou, Jiangtao; Bolisetty, Sreenath; Mezzenga, Raffaele
Abstract : We introduce a green and efficient approach for removing per- and polyfluoroalkyl substances (PFASs) based on the β-lactoglobulin amyloid fibril membrane. Abstract : We introduce a green and efficient approach for removing per- and polyfluoroalkyl substances (PFASs) based on the β-lactoglobulin amyloid fibril membrane. The membrane exhibits superior adsorption capability for long-chain PFASs. At low pH, the membrane efficiency improved significantly due to enhanced electrostatic interactions between positively charged fibrils and negatively charged PFASs. Furthermore, intermolecular adhesion force measurements confirm the hydrophobic–hydrophobic interaction at the nanoscale with PFOS and PFOA representing perfluoroalkyl sulfonic acids (PFSAs) and perfluoroalkyl carboxylic acids (PFCAs), respectively. For real PFAS-contaminated water from the Xiaoqing River basin and under single-step filtration mode, the membrane exhibits high efficiency for removing both high (>μg L −1 ) and trace (ng L −1 ) levels of the compounds. To demonstrate the scalability and generality, a commercial amyloid–carbon-based hybrid membrane is applied for removal of a range of long-chain and short-chain PFASs as well as their replacement compounds, offering complete removal of PFASs with ≥4 perfluorinated carbon atoms in the molecular structure and a removal efficiency of low molecular weight PFBA (3 perfluorinated carbon atoms) exceeding 96%. Analysis of the sustainability footprint reveals the superiority of the amyloid–carbon hybrid membrane for PFAS removal. Altogether, these results demonstrate a high potential of amyloid fibril membrane technology for the sustainable removal of PFASs from water.